'Get Over It'? Racialised Temporalities and Bodily Orientations in Time. (4th March 2019) - Ngo, Helen
ABSTRACT: In this paper I examine the temporal dimensions of racialised and colonised embodiment. I draw on the work of Alia Al-Saji, whose phenomenological reading of Frantz Fanon examines the multiple ways in which racism and colonialism affix the racialised and colonised body to that of the past; a temporalisation that serves not only to anachronise these bodies, but also to close off their projective possibilities for being or becoming otherwise. Such a move reflects the nature of racialisation itself, which following Charles Mills, does not just exteriorise or 'other' racialised bodies, but relies equally on a forgetting, or a disavowal and leaving behind of this very process. The result, I argue, is to render whiteness and white bodies as temporally present and even futural in their orientation, free from the vestiges of racism's history and free to adopt any number of stances on its continuing legacy. It is against this that I argue that the familiar exhortation to 'get over' racism whenever the charge is levelled, is not only dangerous in its denial of racism, but also disingenuous in purporting to move beyond a racially divided world, when in fact this very gesture serves to reinscribe differential racialised temporalities.